(In)visibilidade de espaços festivos: a centralidade da festa de Santo Antônio e as manifestações periféricas de Barbalha, Ceará - Cardoso, Antônio Igor Dantas (2013)
Being the largest expression of the cultural city of Barbalha, Ceará, the Festa de Santo Antônio got, well, great visibility, which concentrates most of the political and cultural sector investments, especially with regard to their patrimony. Other events, such as celebrations of patron, which have structures in their festive designs rituals that remind us of the essential image of the Festa de Santo Antônio, highlighting, emblematically, the ritual sacrifice of the tree: select, cut, and the procession raising of the flag of the patron, the folk groups, among others, remain in the invisibility of these policies, as peripheries of the party chief. Thus, the dynamics of the visible / invisible (Merleau-Ponty, 1980), from the "confrontation" between centers and peripheries festive, providing momentary visibility and invisibility permanent, directed us to think of the municipality of Barbalha from three territories: Sítios Santa Rosa, Cabeceiras e Riacho do Meio, their parties and their historical and geographical representativeness: the movement of bandits materialized in the cemetery of the shot (Alto do Leitão) Sítio Santa Rosa, the strength of traditionalism with devotional Penitentes Irmãos da Cruz do Sítio Cabecerias, icons and environmental protection of the Chapada do Araripe with Ecological Park of the Riacho do Meio. It is noted as justification that we can’t consider the character of the asset visibility Festa de Santo Antônio as the main reason for the invisibility of other manifestations. The challenge on the agenda of this party-main spectacle, to find in other places, the party peripherals, ways to insert them in the processes of cultural appreciation, integrating the processes of historical constitution and memorial in the city. Methodologically, open interviews, semi-structured and projective instigate the subjects of locations, sometimes worked, to talk with their spaces, whether through questions and / or viewing a photographic mural on manifestations of patrimonialidade (POULOT, 2009), gestated for recognition and ownership of the asset by the subjects who experience and represent. Thus, the apprehension of the phenomena analyzed complies with the intent that the subjects involved (revelers) recognize themselves as transformers of their spatialities (MASSEY; KEYNES, 2004). The "symbolic games", representations, values, leisure, trespass, use of spaces, intertwined in the minds of the subjects from language broadcasts festive, like a fertile field for understanding social structures exposed there. The aim is then to understand the logic of the question sheet from the recognition of the individuals who practice it, as belonging to the place, in their lived world (Di Meo, 1996), through their everyday experiences, and among them, the parties.